If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x+20=10x+10
We move all terms to the left:
15x+20-(10x+10)=0
We get rid of parentheses
15x-10x-10+20=0
We add all the numbers together, and all the variables
5x+10=0
We move all terms containing x to the left, all other terms to the right
5x=-10
x=-10/5
x=-2
| 7+7x=-x+63 | | z=8+2z | | 20x+19=9x-3+13x | | -10-7t=-10t+10-t | | 37y=12(3y+5) | | -2-3n=8-4n | | 8x–10=7x | | 9y=6y=6 | | -3(x+2)+3=-3 | | 14x-3=20x-15 | | 16=3t-11t | | -9f+7=-3f-5 | | 10n-3=-8+9n | | -3x=2x-56 | | x+13+5x+1=8x-4 | | 5-7x=2x-31 | | -5-4k=10-7k | | -5(-5+x)=-75 | | -8x=15-(-17) | | g3+-1=-3 | | x-1/x=0.46497 | | 2.5x+.5x=14+3.5x | | 9p=6+6p | | 12x+2=13x-10 | | -10g-6=-7g | | -4t-2=-3t-8 | | (12h)=(-3h+2) | | 5x+7=73-x | | 4n+8n=65 | | -9q-6=-1-8q | | 10-9h=-4h | | 4x-3=6x-7=3 |